Exploring the effects of the built environment on urban community wellbeing - Hassan, Mohammad Mujaheed; Tedong, Peter Aning; Mohd Khir, Azlina; Shari, Zalina; Ponrahono, Zakiah; Sharifudin, Muhammad Phaizal (Human Resource Management Academic Research Society, 2023)
The built environment's impact on urban community wellbeing is a crucial facet of contemporary urbanization. As cities, including those in Malaysia, rapidly expand, the relationship between the built environment and community wellbeing gains prominence. This article explores this dynamic connection, encompassing building, infrastructure, public space, land use planning, accessibility, urban design, and sustainability, affecting residents' quality of life and interactions. In Malaysia, the built environment fosters inclusivity and cohesion amid diverse demographics and cultural richness. Through a systematic approach, this study reviews journal articles to unravel complex relationships between the built environment and community wellbeing. The research offers insights for policymakers, urban planners, and community stakeholders, aiming to inform decision-making and create inclusive urban spaces. By leveraging the built environment strategically, the study advocates for harmonious, thriving urban communities. It emphasizes a paradigm shift in urban planning, prioritizing sustainability, accessibility, and community wellbeing to enhance quality of life for present and future generations.